Mechanical and thermal performance of bio-brick masonry with hydrated lime mortar at high temperature - G. Nakkeeran; L. Krishnaraj; George Uwadiegwu Alaneme; Mustapha Muhammad Lawan (Scientific Reports)
Abstract The construction sector’s growing emphasis on sustainability and thermal efficiency has prompted a shift toward eco-compatible masonry materials. This experimental investigation explores the mechanical and thermal behavior of Bio-Bricks composed of groundnut shell waste (GNS) and hydrated lime mortar under elevated temperature conditions. The study comprehensively evaluates the compressive and shear performance of masonry prisms, as well as heat resistance through prototype wall models. Results reveal that Bio-Bricks combined with hydrated lime mortar deliver a significant enhancement of 7.9% in compressive strength and 12.6% in shear strength over conventional systems. Thermal evaluations demonstrate a reduced indoor heat flux ranging from 8 to 15 °C, indicating superior insulation performance. Furthermore, finite element simulations closely validate experimental results, confirming the reliability of Bio-Brick assemblies under thermal and mechanical stress. The integration of agricultural by-products and pozzolanic binders highlights the potential of Bio-Bricks as a sustainable alternative, promoting energy efficiency and structural reliability in modern construction.